Electrically conductive ZTA–TiC ceramics: Influence of TiC particle size on material properties and electrical discharge machining. (March 2015) - Landfried, R.; Kern, F.; Gadow, R.
Abstract: Processing of highly abrasive materials via powder injection molding or extrusion requires mold materials with high wear resistance to increase the durability of the tools and to sustain a high quality of the manufactured products. High performance ceramics which exhibit high hardness, bending strength and toughness show the perfect combination of properties for these applications. However they also have the usual drawback that they cannot be economically customized in complex shapes and low quantities, as they are required for tool and mold design. Recent material development enabled EDM of electrically conductive oxide ceramics, the most widespread machining process for machining of hard materials, as an alternative to conventional ceramic manufacturing and hard machining technologies. This study focuses on the influence of TiC particle sizes on material properties and EDM machinability of ZTA–TiC ceramics with 24 vol.% TiC, 17 vol.% ZrO2 and 59 vol.% Al2 O3 . Fracture toughness, bending strength and electrical conductivity were analyzed for samples produced from TiC powders with particle sizes varying from 0.43 μm to 2.54 μm. Surface integrity of wire cut samples and feed rate during machining were investigated. It was shown that reducing the size of electrical conductive grains strongly increases the electrical conductivity and slightly decreases mechanical properties. Therefore also the machining characteristics are influenced by TiC grain size. The feed rate increases with decreasing particle size to a maximum at d50  = 1–1.3 μm. Reduction of TiC particle size also leads to significantly decreasing surface roughness after the main cut. Additionally the necessary number of trimming steps to achieve a distinct surface roughness is also minimized for low particle sizes. Highlights: ZTA–TiC ceramics were hot pressed using TiC powders with particle sizes varying from d50  = 0.43 μm to d50  = 2.54 μm. Decreasing TiC particle size slightly decreases toughness and bending strength. Decreasing TiC particle size significantly increases the electrical conductivity. The feed rate increases with decreasing particle size to a maximum at d50  = 1–1.3 μm. Reduction of TiC particle leads to significantly decreasing surface roughness.